The descriptive study of imposter syndrome in medical students of Nishtar Medical University, Multan - Tariq, Ahmed U.; Khan, Hamna; Naeem, Ayesha; Khan, Ali A.; Usama, Ali; Masood, Ayesha (International Journal Of Community Medicine And Public Health, 2025)
Background: Imposter syndrome (IS) is characterized by chronic self-doubt and a fear of being exposed as an intellectual fraud despite evident competence and success. Individuals experiencing this phenomenon often feel they are not as capable as others perceive them to be. In medical education, IS can significantly impact students' learning experiences and mental well-being. This study aims to assess the prevalence and severity of IS among medical students to inform curriculum improvements and support strategies. Methods: A cross-sectional psycho-social analysis was conducted at Nishtar Medical College, Multan, between September and October 2024. After obtaining informed consent, medical students were selected through a random sampling technique. The Clance imposter phenomenon scale (CIPS) was used to assess the incidence and severity of IS. Data were entered and analysed using SPSS v.20. Results: A total of 174 medical students participated, with a 100% response rate. The majority were male (53.4%). Based on CIPS scoring, the severity of IS was categorized as mild (6.3%), moderate (47.1%), severe (39.1%), and very severe (7.5%). The highest prevalence of severe IS was observed among fourth-year students. Conclusions: IS is prevalent among medical students, with a significant proportion experiencing severe symptoms, particularly in their fourth year. The findings suggest that both male and female students are equally susceptible. Given its association with mental health challenges, interventions to support affected students should be considered in medical education.